A discourse analysis of health provider interactions with parents who are reluctant to vaccinate. Issue 5 (May 2022) - Crawford, Tonia; Leask, Julie
Highlights: Discourse analysis of interactions sheds light on key features of communication. Highlights strategic interactional work that displays empathy and builds rapport. Informs educational approaches and builds a repertoire of communication choices. Awareness of discourse strategies can support complex health care consultations. Abstract: Objective: Vaccine hesitancy is a persistent barrier to vaccination uptake, and health professionals report interactions with such parents to be difficult. Using discourse analytic techniques, we examine the foundation of a therapeutic relationship: the display of empathy and attempts to build rapport, in consultations between immunisation specialists and vaccine reluctant parents. Methods: Consultations between consenting clinicians and parents in two Specialist Immunisation Clinics in Australia were recorded. Twelve conversations between the clinicians and parents were analysed using interactional sociolinguistic (IS) discourse analytic methods. Results: This paper takes a case study approach by citing two interactions that exemplify the interactional work of the consultants as they strive to engender mutual understanding and goodwill, noting examples of discursive choices that demonstrate empathy and the building of rapport. Conclusion: Awareness of discourse strategies that interweave relational and clinical goals enable a more nuanced understanding of communication skills that support a guiding partnership in vaccine related decisions with parents. Practical implications: Through highlighting the strategic interactional work that displays empathy and builds rapport, we can inform educational approaches and build a repertoire of communication choices that strengthen the communication skills of health professionals.